Exploring User-Interaction Techniques by Using a Strength Feedback Measurement Device to Encourage Strength Movements of People with Hand Impairments - Chaves, Antonio V; Silva-Calpa, Greis F M; Raposo, Alberto B (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2022)
This study presents a validation and maintenance of a virtual reality game proposed in the literature to assist hand rehabilitation processes. In order to allow direct user interaction, that game uses Oculus Rift and Leap Motion to track the hands. The authors proposed four traditional therapy hand-gestures exercises for user interaction. In this study, we analyzed the game together with physiotherapists, applied changes suggested, added the Myo Armband in order to get the electromyography values on exercises execution, and proposed a new game version. We evaluated the new version with mostly non-disabled people. Results show that participants’ strength increased and they were interested in playing the game more often. Still, some improvements are needed to evaluate the game with patients further.